Host Differential Sensitization toward Color/Lifetime‐Tuned Lanthanide Coordination Polymers for Optical Multiplexing. Issue 52 (25th October 2020) - Ou, Yiyi; Zhou, Weijie; Zhu, Zece; Ma, Fengkai; Zhou, Rongfu; Su, Fang; Zheng, Lirong; Ma, Li; Liang, Hongbin
Abstract: Optical multiplexing based on luminescent materials with tunable color/lifetime has potential applications in information storage and security. However, the available tunable luminescent materials reported so far still suffer from several drawbacks of low efficiency or poor stability, thus restraining their further applications. Herein, we demonstrate a strategy to develop efficient and stable lanthanide coordination polymers (LCPs) with tunable luminescence as a new option for optical multiplexing. Their multicolor emission from green to red and naked‐eye‐sensitive green emission with tunable lifetime (from ca. 300 to ca. 600 μs) can be controlled by host differential sensitization and energy transfer between lanthanide ions. The quantum efficiencies of developed samples range from around 20 % to 46 % and the luminescence intensity/lifetime appear quite stable in polar solvents up to ten weeks. Furthermore, with the aid of inkjet printing and concepts of luminescence lifetime imaging and time‐gated imaging, we illustrate their promising applications of information storage and security in spatial and temporal domains. Abstract : Exploiting the differential sensitization of hosts, stable color/lifetime‐tuned lanthanide coordination polymers have been developed as a novel option for optical multiplexing applications, such as information storage and security. These results will further inspire tunable luminescent materials exploration for optical multiplexing.